Optical Sensor for Analysis of Amonia, Iron and Manganese Nutrients - B Lapsiwala, Pranav; ., . (International Journal of Engineering and Technology, 2018)
The soil nutrients sensor is developed with the help of Light Emitting diodes (LEDs), Photodiode, microcontroller or microprocessor circuit and data logger system. The sensor is working on photometric principle and detects the soil nutrients. The wavelength of LED used as chemical agent and that is reacts with soil sample. The wavelength of LED is useful to detect nutrients like ammonia nitrogen (NHf4-N), iron (Fe), manganese (Mn) by colour changes with the help of different chemical reagent. The resolution of 1.0-20 mg/100 g has been performed for solution of soil nutrients. The samples are taken from different land and results are compared with database created for analysis. Â Â